Diversi Terhadap Anak Yang Melakukan Tindak Pidana Penyalahgunaan Narkotika (Studi Penetapan Pengadilan Negeri Medan) - Faomasi Laia; Madiasa Ablisar; Marlina Marlina; Edy Ikhsan (Iuris Studia: Jurnal Kajian Hukum, 2021)
The legal arrangements regarding diversion for children who have committed criminal acts are contained in several laws and regulations, government regulations, regulations of the Supreme Court which have regulated the procedures for implementing diversion for children who have committed criminal acts. In Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which has explained about diversion, namely as in Article 1 point 7 states that diversion is the transfer of settlement of juvenile cases from the criminal justice process to processes outside of criminal justice The results of this research can be seen, the legal basis for diversion is regulated in Law Number 11 of 2012 concerning the Criminal Justice System for Children, Government Regulation Number 65 of 2015 concerning the Implementation of Diversion and Handling of Children who are not 12 (twelve) years old, and Regulations Supreme Court Number 4 of 2014 concerning Guidelines for the Implementation of Diversion in the Juvenile Criminal Justice System. And in these laws and regulations, the objectives of diversion are stated in article 6 of Law Number 11 of 2012, namely: achieving peace between victims and children, resolving cases of children outside the judicial process, preventing children from being deprived of liberty, encouraging the public to participate , and instill a sense of responsibility in children